2011
DOI: 10.1103/physreva.84.013407
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral fullerenes: A way to control resonant high-order harmonic generation

Abstract: We investigate the high-order harmonic generation in ordinary buckyball C 60 , endohedral In@C 60 fullerene, and endohedral Sb@C 60 fullerene by means of time-dependent density functional theory. In all cases the resonant enhancement of several high-order harmonics in the plateau region up to two orders of magnitude was predicted. Theoretical investigation of absorption spectra of C 60 showed absorption peaks in the regions of the resonant HHG enhancement. In both endohedral fullerenes, peaks of plasmon absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As it was mentioned above, some attempts in explanation of experimental observations of resonance-induced enhancement of single harmonic during plasma HHG have been reported in [43,45,49,[51][52][53][54][55][56][57]. In particular in [53], it has been shown that the influence of atomic autoionizing states on the phase matching of HHG may result in efficient selection of the single harmonic in calcium plasma.…”
Section: Principles Of High-order Harmonic Generation Of Laser Radiatmentioning
confidence: 97%
See 1 more Smart Citation
“…As it was mentioned above, some attempts in explanation of experimental observations of resonance-induced enhancement of single harmonic during plasma HHG have been reported in [43,45,49,[51][52][53][54][55][56][57]. In particular in [53], it has been shown that the influence of atomic autoionizing states on the phase matching of HHG may result in efficient selection of the single harmonic in calcium plasma.…”
Section: Principles Of High-order Harmonic Generation Of Laser Radiatmentioning
confidence: 97%
“…Recent findings of the physical processes driving plasma HHG require systematic analysis of the results reported after previous reviews of this process [33][34][35][36][37]. Those include the harmonic generation in clusters using ablation of commercially available clusters [38,39], fullerenes [40][41][42][43][44][45], and carbon nanotubes [46], enhancement of harmonics from in-situ-produced nanoparticles [47], new resonance-enhanced features of plasma harmonics [48,49], application of high pulse repetition rate sources and ultrashort pulses for the HHG in plasma plumes [21], proposals for the quasi-phase matching of harmonics in plasmas [50], observation of quantum path signatures in harmonic spectra from various ablated targets [22], achievement of µJ level of harmonic energies [28,29], development of few theoretical approaches describing the observed peculiarities of resonance enhancement and fullerene-induced harmonics [43,45,49,[51][52][53][54][55][56][57], observation of extremely broadened high-order harmonics [58], emergence of a "second" plateau in harmonic distribution [59], destructive interference of harmonics in the mixtures of different harmonic emitters inside the plasma [60], measurements of plasma harmonic's pulse duration in the attosecond time scale [32], etc.…”
Section: Early Studies Of Plasma-induced Harmonicsmentioning
confidence: 99%
“…It has been found that confinement oscillations are more prominent in the time delay spectrum than in the cross section [48,60,61], thereby demonstrating the importance of time delay studies in the field of attosecond chronoscopy. Confined systems are predicted to increase the High Harmonic Generation (HHG) yield, underscoring their importance in strong field physics [62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments and theoretical calculations show that benzene molecules are a stable source of harmonics and are also detected when an elliptical polarized driver is used [18]. Experiments and theoretical calculations indicate that fullerene molecules such as C 60 and nanotubes can emit harmonics under different light polarization conditions [11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Recently, HHG in graphene and quantum rings have started to gain attention from both theoretical and experimental points of view [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%